The ecological memory of landscape complexity shapes diversity of freshwater communities - Tabi, Andrea; Santos, Edineusa Pereira [UNESP]; Brejão, Gabriel Lourenço [UNESP]; Siqueira, Tadeu [UNESP] (Wiley, 2025)
Land use change affects the biodiversity of terrestrial landscapes as well as of the freshwater systems they surround, and thereby numerous ecosystem services that are essential for human well‐being. Previous research suggests that freshwater systems show delayed responses to abrupt disturbances such as deforestation, however less is known about whether there is a memory effect of landscape history on freshwater communities under a long history of land use change. We addressed this research gap here by first quantifying the historical complexity of landscapes, including natural and agricultural formations, in terms of their composition and configuration in 26 tropical catchment areas surrounding 101 streams over a 30‐year period. We identified clear evidence for a memory effect of past events, whereby higher historical landscape complexity, measured as the information entropy of landscape composition, led to higher freshwater biodiversity. Finally, using a causal discovery approach, we showed that species richness was causally related to landscape complexity only when historical values were incorporated. Our results corroborate previous work on the positive effect of landscape complexity on biodiversity, and also confirm the role of historical contingencies in predicting future ecological outcomes.